ONLINE PROJECTS AS A FORM OF SPREADING PEDAGOGICAL BIOGRAPHICAL KNOWLEDGE IN THE CONTEXT OF OPEN SCIENCE - Larysa D. Berezivska; Oleksandr P. Mikhno; Olha P. Pinchuk (Інформаційні технології і засоби навчання)
The article deals with the relevant issue of using social media in the context of open science to disseminate the results of scientific research and implement the mission of institutions of social memory – libraries and museums – to preserve, study and popularize the national pedagogical heritage. It has been revealedthat in foreign and Ukrainian historiography there are no special studies on the spread of biographical knowledge in social networks. The online project is considered both as a multifunctional information resource and as a digital tool for educational activities, which, with the help of web technologies, demonstrates specially created open-access content to a wide range of users. For the first time, the paper analyzes the spread of biographical pedagogical knowledge through the development of online projects and their implementation by means of social networks. Biographical online projects of V. O. Sukhomlynskyi State Scientific and Educational Library of the National Academy of Educational Sciences of Ukraine and the Pedagogical Museum of Ukraine are characterized by the following parameters: systematized information in the form of a table (implementation model, name, web resource where the project was implemented, implementation period, hashtag), grouping by type (collective, individual, calendar, thematic), a brief description of the content of each project, a graphic layout of the project. The examples of biographical online projects have been given. The article reveals thetrend of an increase in the number of biographical online projects in the Ukrainian segment of the Facebook social network during 2020–2022, caused by the decolonization of the Ukrainian humanities. 4 proven models for implementing biographical online projects have been proposed for a widespread use: "Online project on Facebook", "Online project on Facebook and Instagram", Online project on Facebook using a web portal/website", Online project on Facebook as a source ofvirtual exhibition on the website". It has been proven that the use of social networks for the dissemination of pedagogical biography in the form of online projects in the educational and scientific space is not only an effective way of providing access to the results of scientific research to a wide audience, but it also contributes to the restoration and preservation of the national memory.